Mindfulness en el tratamiento de trastornos de la conducta alimentaria: revisión aplicada - Ullmann Cedron, Isabella (2023)
Eating disorders (EDs) are a mental health problem, the complexity of which requires a greater focus of attention in their treatment. In recent years, treatments for eating behavior have been developed, including Mindfulness. The present study aims to review the empirical evidence of Mindfulness in the treatment of ED. For this purpose, an applied review was conducted and eleven quantitative investigations were analyzed. The PRISMA methodology (Page et al., 2020) was used for the selection and analysis of the studies. Web of Science (WOS), Scopus, Scielo, ApaPsycnet, Ebsco and ProQuest databases were selected. The selected investigations have moderate to high internal consistency, in terms of the application of their instruments (a = 0.71). The results revealed that mindfulness has a positive impact on reducing the symptomatology of EDs and propose a negative correlation between mindfulness and the different dimensions of EDs